The relationship between emotional intelligence and sports motivation in athletes (Laisvalaikio tyrimai, 2024)
Athletes’ motivation is a dynamic construct that may change due to some factors. For example, the experience of pleasure, enjoyment, competition, and appropriate expectations factors to participate in sports and to achieve high performance (de Franco Tobar, Meurer, & Benedetti, 2013). However, emotional intelligence (EI) also plays a significant role, as athletes experience both positive and negative emotions when faced with achievement, stress, or competitive pressure during sport and competition, which is common in both youth (McCarthy, Allen, & Jones, 2013) and adult sport (Campo et al., 2018). Athletes’ EI may also manifest as an inability to express and manage emotions appropriately (e.g., unbridled anger, aggression, lack of control), particularly in competitive situations itcan negatively affect both athletic performance and withdrawal from sporting activity. Meanwhile, the ability to understand and effectively manage emotions can influence interpersonal relationships within the team better sports performance, and enhance motivation to participate in sports (Ramajayam, 2017). Research purpose – to determine links between athletes’ emotional intelligence and sports motivation.The study involved 245 adult athletes from team sports. Among them were 109 men and 136 women. The mean age of the athletes was 21.8 ± 3.09 years. The following instruments were used in the study emotional intelligence was studied using Schutte Emotional Intelligence Scale (Schutte et al., 1998). Sport motivation was investigated using The sport motivation scale II (Pelletier et al., 2013). Socio-demographic questions about athletes’ age, gender, and represented sport were also provided. Statistical data processing was used to analyse the results.Results. It was determined that the emotional intelligence of athletes is higher than average. It was found that athletes can be most characterised by integrated motivation and least characterised by motivation. Women are more likely to have higher EI compared to men. Women better than men value the ability to control the emotions of others and perceive them. Men all dimensions of sports motivation were statistically significantly higher than for women, except introjected motivation. It was determined that the overall EI and EI dimensions of the participant were statistically significantly related to internal, identified, and injected motivation. The dimensions of their emotion management and perception of emotion are inversely related to motivation .Keywords: emotional intelligence, sports motivation, athletes.